Enhancing Seed Germination and Yield Performance of Onion (Allium cepa L.) under Saline Stress using Plant Growth Regulators and Ascorbic Acid (Journal of the Bangladesh Agricultural University, 2025)
The study aimed to examine the protective role of plant growth regulators and ascorbic acid against NaCl-induced oxidative damage in onion, to enhance its salinity tolerance mechanism. Onion seeds were subjected to salt stress (10 dS/m) and primed with 30 ppm gibberellic acid (GA3), 1-naphthylacetic acid (NAA), salicylic acid (SA), and ascorbic acid (AsA). Additionally, onion plants were sprayed with 100 ppm of these chemicals. The application of 30 ppm GA₃, AsA, and SA significantly enhanced seed germination percentage, vigor, energy of germination, and shoot-root length, while reducing mean germination time. In contrast, NAA negatively affected germination by lowering energy of germination and shoot-root length. The highest germination percentage (87.92%) was recorded with SA, followed by GA₃ at 69.58%, while the lowest (49.17%) was observed in the control and NAA treatments. Foliar application of 100 ppm SA resulted in the highest bulb yield (15.04 t/ha) under saline stress, along with improvements in yield-contributing parameters. This yield was statistically similar to those obtained from GA₃ and AsA treatments. In contrast, NAA treatment showed no significant difference from the control. The study highlights SA as a potential PGR for improving onion productivity, offering a valuable approach for mitigating salt stress in onion cultivation.J Bangladesh Agril Univ 23(3): 296–303, 2025